결혼이민자의 사회적 활동참여가 생활만족도에 미치는 영향: 사회적 관계의 매개효과를 중심으로 - 임동진(Lim, Dong-Jin); 박관태(Park, Kwan-Tae) (한국조직학회보, 2022)
본 연구의 목적은 결혼이민자들의 생활만족도에 영향을 미치는 요인들을 분석하고, 사회적 활동참여와 생활만족도 간 관계에서 사회적 관계가 매개역할을 하는지를 규명하고, 이를 토대로 이론적･정책적 함의를 제시하는 것이다. 이를 위해 2018년 우리나라에 거주하는 결혼이민자 3,731명에 대한 설문자료를 분석하였다. 본 연구의 주요 연구결과를 요약하면 다음과 같다. 첫째, 우리나라 결혼이민자들의 인구･사회학적 특성은 여성, 30대, 고졸 이하, 5∼10년 미만의 혼인 기간, 4~5명의 가구원 수, 13.5/20점의 한국어 실력을 보인다. 둘째, 결혼이민자들은 언어소통에 어려움이 있고, 자신의 사회적 지위가 낮고, 사회적 활동참여가 적으며, 생활만족도는 보통이라고 인식하였다. 셋째, 결혼이민자의 생활만족도에 영향을 미치는 주요 변수는 가족과의 관계, 사회적 지위, 우울증 경험 정도, 자녀와의 관계였다. 즉, 결혼이민자 중 가족과의 관계가 좋을수록, 사회적 지위가 높다고 인식할수록, 우울증 경험이 적을수록, 자녀와의 관계자 좋을수록 이들의 생활만족도가 높게 나타났다. 마지막으로, 결혼이민자의 사회적 활동참여가 많을수록 이들의 생활만족도가 높게 나타났다. 또한, 결혼이민자의 사회적 활동참여와 생활만족도 간 관계에서 가족과의 관계라는 매개변수가 매개역할을 하면서 이들의 생활만족도를 높이는 것으로 나타났다. The purpose of this study is to analyze the factors affecting marriage immigrants' participation in social activities and life satisfaction, and to investigate whether social relationships play a mediating role in the relationship between social activity participation and life satisfaction. Also, based on this, theoretical and policy implications are presented. For this purpose, this study analyzed questionnaire data on 3,731 marriage immigrants living in Korea in 2018. The main research results of this study are summarized as follows. First, the demographic and sociological characteristics of marriage immigrants in Korea are female, in their 30s, under high school graduation, married for less than 5-10 years, number of 4-5 household members, and Korean language proficiency score of 13.5/20. Second, marriage immigrants felt difficulties with language problems, perceived that their social status was low, their participation in social activities was relatively low, and their overall life satisfaction was average. Third, the main variables affecting the life satisfaction of marriage immigrants were family relationship, social status, degree of depression experience, and relationship with children. That is, among marriage immigrants, the better their relationship with their family, the higher their social status, the less they experienced depression, and the better their relationship with their children, the higher their life satisfaction. Finally, the more marriage immigrants participated in social activities, the higher their life satisfaction was. In addition, in the relationship between marriage immigrants' participation in social activities and their life satisfaction, the parameter of relationship with family played a mediating role, increasing their life satisfaction. KCI Citation Count: 1